1987
DOI: 10.1152/jappl.1987.63.2.707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of airway wall flexibility on clearance by simulated cough

Abstract: In our previous study, we investigated the relationship between mucus rheology, depth of mucus layer, and clearance by simulated cough. The purpose of the present study was to examine the effect of airway wall flexibility on the clearance of mucuslike gels. Transient airflows similar to cough were generated by both positive and negative pressure, the latter to mimic the dynamic compression that occurs during real cough. As in the previous study, the trachea was modeled as a trough of rectangular cross section … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Figure 6 shows flow, area and velocity curves in a representative trachea in the test chamber during an artificial cough. The reduction of cross-sectional area by dynamic compression during maximum flow contributed substantially to the achievement of high flow velocity [24]. The calculated velocity curve for a completely rigid trachea underscores the importance of this effect.…”
Section: Discussionmentioning
confidence: 81%
“…Figure 6 shows flow, area and velocity curves in a representative trachea in the test chamber during an artificial cough. The reduction of cross-sectional area by dynamic compression during maximum flow contributed substantially to the achievement of high flow velocity [24]. The calculated velocity curve for a completely rigid trachea underscores the importance of this effect.…”
Section: Discussionmentioning
confidence: 81%
“…However, during cough, the trachea can contract and relax, due to tracheal wall flexibility. The effect of airway wall flexibility on the clearance of mucus-like gels has been analysed by Soi.AND et al (16) who demonstrated that the efficiency of cough clearance is directly related to airway wall flexibility, the higher the flexibility, the more efficient the clearance. In fact, the rapid successive cough manoeuvres that we carried out are somewhat different from that existing in vivo where there is a decrease in peak flow rate per cough in parallel with the fall in lung volume.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, a flexible bottom wall was incorporated in the model trachea. 27 When air pressure outside the tracheal model wall (as in the intrathoracic airways) was more positive than inside, the wall was pushed inward during the cough maneuver. This had the effect of accelerating the airflow, enhancing clearance.…”
Section: Fig 1 Effects Of Flutterா Valve Oscillations (30 Min) and mentioning
confidence: 99%